Blotter test: Test for seed-borne fungi - International Rice Research Institute Seed Health and Logistics Unit (International Rice Research Institute, 2024)
This work instruction (WI) describes the step-by-step process for the detection of seedborne fungi using the blotter method. The blotter method is widely used for detecting fungi which are able to produce mycelial growth and fruiting structures under the incubation conditions described in the test.